2013
DOI: 10.1097/ajp.0b013e318258993e
|View full text |Cite
|
Sign up to set email alerts
|

Gastroretentive Gabapentin (G-GR) Formulation Reduces Intensity of Pain Associated With Postherpetic Neuralgia (PHN)

Abstract: Once-daily G-GR 1800 mg was effective and well tolerated for the relief of pain in patients with postherpetic neuralgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 18 publications
0
59
0
Order By: Relevance
“…Given the relatively small number of discontinuations attributed to AEs during the first week of treatment (2.4% in the placebo arm vs 4.7% in G-GR arm), it would seem that AEs were manageable for most women and that the more rapid 1-week titration used in this study (as opposed to the 2-wk titration used in studies of G-GR in postherpetic neuralgia) 14 was suitable for this population of highly symptomatic women, who are younger and generally healthier. The low propensity for drug interactions is also an important component of the safety profile of gabapentin.…”
Section: Safety and Tolerabilitymentioning
confidence: 87%
See 1 more Smart Citation
“…Given the relatively small number of discontinuations attributed to AEs during the first week of treatment (2.4% in the placebo arm vs 4.7% in G-GR arm), it would seem that AEs were manageable for most women and that the more rapid 1-week titration used in this study (as opposed to the 2-wk titration used in studies of G-GR in postherpetic neuralgia) 14 was suitable for this population of highly symptomatic women, who are younger and generally healthier. The low propensity for drug interactions is also an important component of the safety profile of gabapentin.…”
Section: Safety and Tolerabilitymentioning
confidence: 87%
“…10,13 The slower release afforded by the gastroretentive formulation seems to enhance tolerability and permits a more rapid titration to an efficacious dose. 14 A phase 2 dose-finding clinical study of G-GR in women with VMS 15 demonstrated that 1,800 mg/day was efficacious and had fewer adverse effects than 2,400 mg/day. Earlier phase 3 placebo-controlled studies comparing 1,200 mg once daily and 1,800 mg dosed asymmetrically twice per day (600 mg AM/ 1,200 mg PM) found that the 1,800-mg dose was more efficacious than the 1,200-mg dose and was well tolerated.…”
mentioning
confidence: 99%
“…Integrated data from two RCTs (Phase 3, double-blind, randomized, placebo-controlled studies 81-0045 and 81-0062; clinicaltrials.gov identifiers NCT00335933 and NCT00636636) [16,22] and one realworld study (Phase 4, open-label, single-arm study 81-0067) [23] were compared in this analysis. All studies shared a similar G-GR treatment schedule, which included a 2-week titration period, a stable-dose treatment period (8 weeks for the Phase 3 studies and 6 weeks for the Phase 4 study), and a 1-week dose tapering period.…”
Section: Study Design and Treatmentmentioning
confidence: 99%
“…Detailed patient selection criteria for individual studies have been previously published [16,22,23]. Briefly, men or women aged ≥18 years were eligible to enter the Phase 3 or 4 studies.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation